B-Cell Lymphoma Producing IgM Anti-B Antibody: A Case Report - Jiang, Feiyu; Song, Tiejun; Wang, Yingjian; Liu, Zhiwei (Frontiers in Medicine, 2022)
ABO blood group system is the most important blood group system in transfusion and transplantation medicine. Diffuse large B-cell lymphoma (DLBCL) is the most common type of non-Hodgkin lymphomas (NHLs) worldwide. There have been some studies that lymphoma could affect ABO blood group system and thus affect blood transfusion strategy. However, the mechanisms lymphoma affecting ABO blood group system have not been fully elucidated so far. Here, we report a case of a patient who was a 72-year-old Chinese man came to our hospital for medical advice because of cervical lymphadenophathy. The patient was subsequently diagnosed with diffuse large B-cell lymphoma by lymph-node biopsy. His ABO blood group was initially typed as B on November 7, 2020. He was transfused B type leukocyte poor RBCs (LPR) before we found the patient’s ABO blood group discrepancy on December 2, 2020 by forward and reverse typing methods, which the discrepancy was verified by genotyping. The patient began to transfuse O type washed RBCs (WRBC) since then. Compared to transfuse B type leukocyte poor RBCs (LPR), the efficiency of transfusing O type washed RBCs (WRBC) was better. Although hemoglobin level did not greatly improve, indirect bilirubin level evidently decreased. Furthermore, we found B-cell lymphoma affected blood transfusion strategy by producing IgM anti-B antibody in this case. Clinicians should need to be aware of the effect of B-cell lymphoma on blood transfusion strategy.